CO2 turned into a nitrogen doped carbon catalyst for fuel cells and metal–air battery applications. Issue 12 (26th May 2021) - Ratso, Sander; Walke, Peter Robert; Mikli, Valdek; Ločs, Jānis; Šmits, Krišjānis; Vītola, Virgīnija; Šutka, Andris; Kruusenberg, Ivar
Abstract : Carbon dioxide is turned into a promising metal-free catalyst for fuel cells via molten salt electrolysis. Abstract : Heteroatom doped metal-free catalysts are one of the most promising replacements for platinum for the alkaline oxygen reduction reaction (ORR). Due to the lack of metal atoms, they are extremely stable and environmentally friendly. However, production of carbon nanomaterials can have a very high CO2 footprint. In this study, we present ORR catalysts made directly from CO2 via molten salt CO2 electrolysis. The deposited carbon powder is doped with nitrogen using pyrolysis in the presence of dicyandiamide. The effect of molten carbonate electrolyte composition towards the final ORR activity in 0.1 M KOH is studied. A thorough physico-chemical study of the starting carbons and N-doped catalysts is presented with SEM and TEM imaging, BET analysis, Raman and X-ray photoelectron spectroscopy as well as the rotating disk electrode method. The onset potential and half-wave potential of the better catalyst were −50 and −175 mV vs . SCE in 0.1 M KOH, respectively.